Margaret Buckingham, discoveries in skeletal and cardiac muscle development, elected to the National Academy of Science - Rudnicki, Michael A (Université d'Ottawa | University of Ottawa, 2012)
Abstract Margaret Buckingham was presented as a newly elected member to the National Academy of Sciences on 28 April 2012. Over the course of her career, Dr Buckingham made many seminal contributions to the understanding of skeletal muscle and cardiac development. Her studies on cardiac progenitor populations has provided insight into understanding heart malformations, while her work on skeletal muscle progenitors has elucidated their embryonic origins and the transcriptional hierarchies controlling their developmental progression.